ANALISIS PENETAPAN HAKIM TERHADAP PENOLAKAN ASAL USUL ANAK DALAM PRESPEKTIF MAQASHID SYARI’AH - nailul muna (At-Ta'aruf : Jurnal Hukum Keluarga Islam, 2023)
At the establishment of the wonosobo religion, a proclamation for the origin of child number 448/ pdt.p /2021/ pa.Wsb. The magistrate's court of justice at the wonosobo religion has refused to grant all the petition, confirming a couple want to validate sirri's child's marriage as their legal child. This kind of research is field research. Primary data used is the wonosobo case file number 448/ pdt. p /2021/ pa. Wsb and an interview with the judges dropping the case. The data-collection technique of interviews and documentaries. Whereas the analytical techniques use descriptive analysis. Results of such studies: 1.) wonosobo religious court number 448/ pdt.p /2021/ pa. Wsb in the quest for the origins of children is still unable to provide justice and benefits to the justice seeking community. It had not been able to provide protection especially to the child, when the child was born from the legal marriage of sirri, only the marriage of her was not met by the state law, since the man was "still the husband of another" but had been divorced orally. Such restrictions or requirements are actually temporary ones, as explained in mk no. 46/ puu-viii /2010) that "children born out of wedlock have a civil relation with their mother and the family of their mother should be read The child born out of wedlock has a civil relation with his biological mother and father and his two families "and in the presectarian maqa ṣid 'ah this ruling can result in interference with the five most basic subjects according to priest Asy-Syatibi.